Sustainable Economic Growth: Bridging Innovation, Strategy, and Implementation in a Globalized World - Putra, Abellando Biyakto; Putri, Salsabiela Amanda; Mas’ud, Fuad; Yuniawan, Ahyar (LifeSciFi, 2025)
Sustainable economic growth increasingly relies on intangible factors like corporate culture and employee engagement. This article explores how organizational values, beliefs, and behaviors—along with employees' emotional connection to their work—impact innovation, strategic alignment, and sustainability implementation. Drawing on literature from 2015–2025 and global data, we analyze these dynamics at both organizational and macroeconomic levels. A strong, innovation-driven culture aligned with strategic goals enhances performance and adaptability. Engaged employees, in turn, drive motivation, productivity, and creativity, linking high-level strategy with operational execution. We highlight how inclusive cultures foster risk-taking and knowledge sharing, essential for innovation. Additionally, we examine how culture and engagement influence strategy execution, often determining whether well-designed strategies succeed or fail. In sustainability contexts, embedding CSR and ESG values into corporate culture and actively involving employees is vital for achieving long-term goals. On a national scale, widespread employee engagement and strong corporate cultures support productivity, innovation, and advancement toward global sustainability targets. The article concludes by emphasizing the critical role of leaders and policymakers in cultivating these cultural and engagement drivers to achieve sustainable economic growth. Further readings are available in the footnotes and bibliography.